Animal accumulators from the perspective of health promotion and surveillance - Rodrigues, Claudio Manuel (ABCS Health Sciences, 2019)
Animal accumulation is considered a complex phenomenon that, although recognized in the academic universe, is still difficult to solve for health management. Studies on accumulation, mainly of animals, are incipient in Brazil. This literature review article aims to warn about this complex morbidity, which is increasingly common to urban agglomerations, indicating health promotion and surveillance actions to ensure the health of animals, the accumulator and the community to which it belongs. It is suggested that a new approach to animal accumulation disorder may counteract the poor - including academic - visibility demonstrated in the literature review, increasing investment in specific interventions that may explain this important public health problem in Brazil.